Characterizations of Besov-Type and Triebel-Lizorkin-Type Spaces by Differences - Douadi Drihem (Journal of Function Spaces and Applications, 2012)
We present characterizations of the Besov-type spaces 𝐵𝑠,𝜏𝑝,𝑞 and the Triebel-Lizorkin-type spaces 𝐹𝑠,𝜏𝑝,𝑞 by differences. All these results generalize the existing classical results on Besov and Triebel-Lizorkin spaces by taking 𝜏=0.